Transformasi Kekuasaan Dan Kebudayaan Di Era Umayyah: Dari Arabisasi Hingga Pusat Peradaban Damaskus - Jufri, Rina Fauziah (UIN Sumatera Utara, 2025)
The Umayyad dynasty (661-750 AD) was an important milestone in the early history of Islamic civilization that underwent a major transformation from an elective caliphate system to a centralized hereditary monarchy. This research aims to examine historically the transformation of power and cultural policies during the Umayyad period, especially related to Arabization, Islamization, and the role of Damascus as the center of Islamic civilization. The method used is a qualitative-descriptive approach with literature study techniques from relevant sources. The results showed that the Arabization policy, which included the uniformity of administrative language and bureaucratic system, played a major role in building the political and cultural unity of Muslims. Meanwhile, the Islamization process expanded the influence of Islam to Asia, Africa and Europe, as well as creating social dynamics between Arab and non-Arab Muslims (mawali). Damascus developed into a cosmopolite cultural center through the acculturation of Arabic, Byzantine and Persian cultures. This transformation laid the foundation for an inclusive and multicultural global Islamic civilization.